Gallstone ileus, the forgotten one: a rare cause of intestinal perforation and a case report - Guevara Valmaña, Osvaldo Ivan; Beyuma Mora, Hugo Enrique; Chavez, Chantal Gonzalez; Murguia Zamora, Laura Maria; Gil Loaeza, Elias; Palacio Pizano, Luis Fernando (International Journal of Research in Medical Sciences, 2020)
Gallstone ileum represents an unusual cause of intestinal obstruction as a result of the presence of stones that cause mechanical obstruction. It has an incidence of less than 4%. Reaching mortality up to 25% of cases. It is a difficult suspicion, with characteristic signs that guide its presence such as pneumobilia, occlusion, and the presence of stone in radiological studies. Management should include surgical extraction as well as revision of the entire intestine with a suitable subsequent repair. Authors present the case of a 70-year-old patient with the presence of surgically resolved biliary ileum.